2021
DOI: 10.1186/s40798-020-00297-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consuming Carbohydrate With and Without Protein on the Rate of Muscle Glycogen Re-synthesis During Short-Term Post-exercise Recovery: a Systematic Review and Meta-analysis

Abstract: Background Rapid restoration of muscle glycogen stores is imperative for athletes undertaking consecutive strenuous exercise sessions with limited recovery time (e.g. ≤ 8 h). Strategies to optimise muscle glycogen re-synthesis in this situation are essential. This two-part systematic review and meta-analysis investigated the effect of consuming carbohydrate (CHO) with and without protein (PRO) on the rate of muscle glycogen re-synthesis during short-term post-exercise recovery (≤ 8 h). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…For example, in the study, it is shown in that for Basmati rice and Arborio rice, it could be suggested to use stewing in order to improve the percentage of amylose with respect to total carbohydrates. On the contrary, in other contexts, it could be useful to favor cooking methods that induce a reduction of the percentage of amylose with respect to total carbohydrates, in order to increase carbohydrates availability and to contribute to recovery after physical exercise [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the study, it is shown in that for Basmati rice and Arborio rice, it could be suggested to use stewing in order to improve the percentage of amylose with respect to total carbohydrates. On the contrary, in other contexts, it could be useful to favor cooking methods that induce a reduction of the percentage of amylose with respect to total carbohydrates, in order to increase carbohydrates availability and to contribute to recovery after physical exercise [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our conclusions regarding AUCg and slope should be interpreted with some caution as the first two salivary samples of the day were not obtained accurately. As a result, the cortisol awakening response [ 64 ] was not evaluated in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion in the glycogen content in organisms exposed to atrazine and compared to the control group, is an indication of probable toxicological effect as observed in oxidative stress. The reduction in glycogen levels of tadpoles exposed to atrazine could be the result of the pesticide affecting the activities of enzymes that work in glycogenolysis (Craven et al, 2021). Some investigations have also showed that organic contaminants like pesticides could decrease the glycogen level of invertebrates and fish by affecting the activities of enzymes that play active role in the carbohydrate metabolism (Cicik & Engin, 2005).…”
Section: Discussionmentioning
confidence: 99%